To study pattern of obstetric cases referred at tertiary care centre in Central India - Goswami, Prakriti; Bindal, Jyoti; Chug, Niketa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal morbidity and mortality remains a major challenge to health systems worldwide. Referral services for identification and referral of high risk pregnancies are an integral part of maternal and child health services. Timeliness and appropriateness of referral are challenge to obstetricians, since delay in referral affects maternal outcome adversely, hence the identification of at risk patients and obstetric emergencies and their timely referral is of immense importance. The aim of this study was to review the pattern of obstetric cases referred to tertiary care centre, to identify their clinical course, mode of delivery and maternal outcomes. Methods: It was prospective observational study carried out from January 2015 to July 2016. Study population was all Obstetrics patients referred to Department of Obstetrics and Gynecology of Kamla Raja Hospital, G.R. Medical College, Gwalior, Madhya Pradesh, a tertiary care centre during the study period. Results: The total number of referred cases in above study period was 4085.The proportion of referred cases in the tertiary care hospital was 20.86%. Mode of transport used by the referred patients were hospital ambulances (38%) and private vehicles (62%). Most common diagnosis at the time of referral was anaemia (27.8%). Out of the total referred cases, 48% had vaginal delivery (either spontaneous or induced), 28% had caesarean section and 24% were managed conservatively. Hypertensive disorders (25.4%) constitutes the leading cause of maternal deaths amongst the referred cases. Conclusions: Peripheral health care system needs to be strengthened and practice of early referral needs to be implemented for better maternal outcome.